Nephroprotective Effects of Piperlongumine against Streptozotocin-Induced Diabetic Kidney Disease in Rats - Xu, Yang; Zheng, Xijie; Hao, Zhenzhen (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Diabetes mellitus is a chronic metabolic disorder defined by hyperglycemia, potentially resulting in various consequences, such as diabetic kidney disease. Diabetic kidney disease is a major health concern associated with heightened morbidity and mortality risk. Aim/Objectives: The current study was performed to study the beneficial effects of piperlongumine against Streptozotocin (STZ)-induced diabetic renal dysfunction and renal fibrosis in an experimental rat model. Materials and Methods: In the present study, rats were injected with 45 mg/kg of STZ, and subsequently administered with piperlongumine for 8 weeks. Upon conclusion of the treatments, the body weight, feed and water consumption, glucose, and insulin concentrations of the experimental rats were assessed. The biomarkers for renal impairment, such as kidney index, creatinine, urine albumin, Blood Urea Nitrogen (BUN), and oxidative markers were evaluated using commercial assay kits. The renal tissues of the experimental rats underwent histological examinations to evaluate the histological changes, renal interstitial fibrosis, and glomerulosclerosis levels in the kidneys. Results: The treatment of piperlongumine considerably increased body weight and subsequently reduced food and water consumption, glucose, and insulin in STZ-induced rats. In addition, the piperlongumine treatment reduced the amounts of renal function markers and considerably augmented the renal antioxidant levels in rats with diabetic nephropathy. Furthermore, the histopathological studies also evidenced that piperlongumine treatment can hinder renal fibrosis and glomerulosclerosis in diabetic nephropathy rats. Conclusion: The current results suggest that piperlongumine may considerably alleviate diabetic kidney disease in rats. Therefore, the present findings indicate that piperlongumine can be a useful treatment option for diabetic nephropathy.
Keywords: Glomerulosclerosis; Piperlongumine; Hyperglycemia; Streptozotocin; Insulin